2014
DOI: 10.3174/ajnr.a3857
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive versus Bare Platinum Coils in the Treatment of Intracranial Aneurysms: The MAPS (Matrix and Platinum Science) Trial

Abstract: EBM 1 ABSTRACT BACKGROUND AND PURPOSE:The ability of polymer-modified coils to promote stable aneurysm occlusion after endovascular treatment is not well-documented. Angiographic aneurysm recurrence is widely used as a surrogate for treatment failure, but studies documenting the correlation of angiographic recurrence with clinical failure are limited. This trial compares the effectiveness of Matrix 2 polyglycolic/polylactic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 21 publications
5
84
0
Order By: Relevance
“…What is not surprising in these high-risk patients, angiographic outcomes were inferior compared with those in other coiling trials. 16,17,22,23 Safety endpoints were similar for the 2 groups, except for a greater number of deaths unrelated to the aneurysm or treatment (7 versus 1) in the hydrogel group. A careful review of individual cases indicates that this difference is probably a chance finding.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…What is not surprising in these high-risk patients, angiographic outcomes were inferior compared with those in other coiling trials. 16,17,22,23 Safety endpoints were similar for the 2 groups, except for a greater number of deaths unrelated to the aneurysm or treatment (7 versus 1) in the hydrogel group. A careful review of individual cases indicates that this difference is probably a chance finding.…”
Section: Discussionmentioning
confidence: 76%
“…15 Recurrent aneurysms after platinum coiling are at high risk of re-recurring when retreated, but these patients were excluded from all published randomized trials. 8,14,[16][17][18] The Patients Prone to Recurrence After Endovascular Treatment (PRET) study was designed in 2007 to offer an alternative to platinum coiling in patients previously shown to be at high risk of recurrence: patients with large (Ն10 mm) or recurrent aneurysms after coiling. The trial protocol was published in 2008.…”
mentioning
confidence: 99%
“…4 Between the time of the initial treatment and the 1-year follow-up, of 484 aneurysms, 176 (36%) exhibited worsening occlusion, 167 (34%) showed no change, and 141 (29%) improved. Despite the significant rates of residual aneurysm filling reported in all 3 trials, the rehemorrhage rates in patients with ruptured aneurysms are very low.…”
mentioning
confidence: 99%
“…Importantly, in MAPS, residual aneurysm filling (Raymond class 3) was a strong predictor of the composite primary end point of the Target Aneurysm Recurrence (TAR) trial. 4 Overall, the best endovascular results, including those for treatment of ruptured and unruptured aneurysms, show complete obliteration < 60% of the time.…”
mentioning
confidence: 99%
“…Multiple trials, including the MAPS (Matrix and Platinum Science) trial and the Cerecyte trial, have failed to show a decrease in recurrence based on coil types. 4,5 The HELPS (Hydrogel-coated coils versus bare platinum coils for the endovascular treatment of intracranial aneurysms) trial demonstrated that hydrogel coils did not reduce late aneurysm rupture or improve outcome compared with bare-metal coils. 7 Even though one coil type has not been proven superior to another coil type, industry uses various pricing for similar types of coils.…”
Section: Discussionmentioning
confidence: 99%